PERANCANGAN KOLEKSI UNTUK BRAND SYMPTOMS BAGI PRIA PENGGEMAR TRAVELLING - Purnomo, Monika Gabriela; Tjandrawibawa, Paulina (Jurnal VICIDI, 2020)
The collection is designed to introduce Symptoms brand to people, especially men who like travelling so that they aware of the existence of the brand and its products. Indonesian people like to travel and this is supported by data that show significant increase in travelling activity from year to year. Therefore, Symptoms wants to use this opportunity to introduce their travel outfit that can help men to do their travelling activity in more practical way and also to contribute positively to the fashion industry in Indonesia.